2022
DOI: 10.1111/1759-7714.14760
|View full text |Cite
|
Sign up to set email alerts
|

LINC02323 facilitates development of lung squamous cell carcinoma by miRNA sponge and RBP dysregulation and links to poor prognosis

Abstract: Background The poor outcome of patients with lung squamous cell carcinoma (LUSC) highlights the importance of the identification of novel effective prognostic markers and therapeutic targets. Long noncoding RNAs (lncRNAs) have generally been considered to serve important roles in tumorigenesis and the development of various types of cancer, including LUSC. Methods Here, we aimed to investigate the role of LINC02323 in LUSC and its potential mechanisms by performing comprehensive bioinformatic analyses. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…With bioinformatics analysis and multiple software predictions, we identified miR-6783-3p as the potential downstream mechanism of circPRKD3. miR-6783-3p was demonstrated to sponge circ_0006427 and LINC02323 to modulate tumor proliferation, migration, and invasion [ 42 , 43 ]. In addition, miR-6783-3p could target CYP2C19 to regulate clopidogrel resistance in patients with cardiovascular diseases [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…With bioinformatics analysis and multiple software predictions, we identified miR-6783-3p as the potential downstream mechanism of circPRKD3. miR-6783-3p was demonstrated to sponge circ_0006427 and LINC02323 to modulate tumor proliferation, migration, and invasion [ 42 , 43 ]. In addition, miR-6783-3p could target CYP2C19 to regulate clopidogrel resistance in patients with cardiovascular diseases [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINC02323 is thought to promote cell growth and migration of ovarian cancer via TGF-β receptor 1 by miR-1343-3p (32). Additionally, Wu et al found that LINC02323 facilitated the development of lung squamous cell carcinoma by miRNA sponge and RNA-binding protein dysregulation, and was linked to poor prognosis (33). lncRNA GPC5-AS1 is believed to stabilize GPC5 mRNA by competitively binding with miR-93/106a to suppress gastric cancer cell proliferation (34).…”
Section: Discussionmentioning
confidence: 99%